Bridging the gap for transtibial prosthetic rehabilitation : analysis for the development of a pro bono application - Van Vuuren, Susanna Catharina (Stellenbosch : Stellenbosch University, 2023)
Thesis (MHumanRehabSt)--Stellenbosch University, 2023.